Մատենադարանի Ալ. Երիցյանի արխիվ. «Հյուսիսափայլ» ամսագրի հրատարակման նախապատմությունը - Հովհաննիսյան, Հայկազ (Մատենադարան)
One of the volumes of the archive of Al. Yeritsyan at the Mashtots Matenadaran preserves documents that reveal the important circumstances and background of the publication of the Armenian journal Northern Lights by Stepanos Nazaryants in 1857. The story starts with a letter-petition of Stepanos Nazaryants dated March 13, 1856, to the Minister of Public Education of Russia Norov, in which he detailed his intention to publish a journal in modern Armenian in Moscow. The Russian government did not create particular obstacles for the Armenian sholar to publish the journal, which seems a little strange for those times, bearing in mind the fact that Nazaryants belonged to the liberal wing of the Armenian national movement. In the petition of St. Nazaryants detailed the goals and objectives of the new edition; he presented it not as a social-political, but as a literary journal, a periodical for Armenians living in Russia, which should serve to provide information on Russian education, “informing my compatriots about the Russian science, introducing the Russian thought and life to them,” as writes Nazaryants. Although in his letter St.Nazaryants shows obvious intention for serving the Russian government, one should not exaggerate the role of his “praise” of Russian culture and accuse Nazayants of Russophilia. His Armenological heritage is dominated by the patriotic attitude in the matters of national culture and education. Finally, on the basis of the conclusions of the Caucasian Educational Inspectorate, the Audit Commission of the Office of the vicegerent of the Caucasus and the Ministry of Public Education, on August 13,1857 Emperor Alexander II approved the petition of the professor of the Lazaryan Institute of Oriental Languages St. Nazaryants to publish the journal Northern Lights in modern Armenian, according to the planned program. However the Northern Lights was later published without the fifth point proposed by the Russian governers, which was supposed to elucidate the “government decisions.” В одном из томов архива Ал. Ерицяна в Матенадаране имени Маштоца хранятся документы, раскрывающие важные обстоятельства и предысторию издания Степаносом Назарянцем журнала “Северное сияние” в 1857 году. Все начинается с письма-прошения Степаноса Назарянца от 13 марта 1856 г., адресованного министру народного просвещения России А. С. Норову, в котором Ст. Назарянц подробно излагает свое намерение издавать в Москве журнал на современном армянском языке. Российские власти не создают армянскому ученому особых препятствий, несмотря на факт принадлежности Ст. Назарянца к либеральному крылу армянского национального движения. В прошении Ст. Назарянц подробно изложил цели и задачи нового издания; примечательно, что он представил его не как общественно-политический, а как литературный журнал, периодическое издание для проживающих в России армян, которое должно служить информационному обеспечению российского образования, “о плодах науки приобщения соотечественников к русской мысли и жизни”, как пишет Назарянц. На основании заключений Кавказской образовательной инспекции, Ревизионной комиссии Канцелярии наместника Кавказа и Министерства народного просвещения, император Александр II 13 августа 1857 года дал положительный ответ на прошение профессора Лазаревского института восточных языков Степаноса Назарянца об издании журнала “Северное сияние” на современном армянском языке по намеченной программе, однако журнал впоследствии публиковался без предложенного российскими властями пятого раздела, который должен был освещать “решения правительства”.
Keywords: Պատմություն